An Eulerian model for the motion of granular material with a large Stokes number in fluid flow. (June 2017) - Ku, Kum-Song; An, Chol-Ho; Li, Kum-Chol; Kim, Myong- Il
Highlights: For the granular flow with a large Stokes number, unilateral incompressibility is applied and discrete formulation for the numerical analysis is proposed. The granular flow equation is discretized using the SPH method for the convergence and applicability on the unstructured mesh. An optimization problem for solid pressure is obtained from unilateral incompressibility condition and by solving it, the solid pressure field is determined. Abstract: This study introduced a novel Euler–Euler approach for modeling granular multiphase flow. The motion of particles with a large Stokes number was investigated assuming that granular material has unilateral compressibility. Solid pressure in the momentum equations for granular multiphase flow was determined so that the unilateral incompressibility condition was satisfied. Using the continuity condition of the granular phase, the equation was rewritten in the optimal form to calculate the solid pressure. A discrete formulation of smoothed particle hydrodynamics was applied for the convective terms so that the discrete matrix was positive semidefinite for the convergence and the discretization for an unstructured mesh was allowed. Frictional stress was then determined from solid pressure and, by using the solid pressure and frictional stress, momentum equations for the granular phase were solved. The method was incorporated into ANSYS FLUENT by a UDF (user defined function). Model validation was performed through a comparison with two previous results, and efficacy of the proposed model was confirmed.